THE CONTRIBUTION OF THE BEEF CATTLE FARMING SECTOR TO HOUSEHOLD INCOME IN THE TEAK FOREST AREA (CASE STUDY IN THE KEDUNGADEM SUB-DISTRICT, BOJONEGORO REGENCY) - T Y Azmi; Anie Eka Kusumastuti; B A Nugroho; E Nugroho (Agricultural Socio-Economics Journal, 2022)
Limited employment opportunities in rural areas make it more challenging for people to live a prosperous life. The social and economic conditions of rural communities tend to depend on the agrarian sector, such as the livestock sector. The livestock sector as an agricultural sub-sector is a very strategic and reliable way to create economic growth, reduce unemployment and create additional sources of income for the community. Most of the population of the Kedungadem sub-district in the Bojonegoro Regency work in the agricultural sector, for example in livestock farming. This study reveals the total income of cattle farmers’ households and the contribution of income derived from beef cattle farming activities to the total household income of farmers who live in the teak forest area. One hundred beef cattle farmers were randomly selected and grouped into one of three beef cattle farming scales, based on the number of cattle owned. This study shows that the average total income in scales I, II, and III was IDR. 19,211,392.15/year, IDR. 34,583,874.51/year, and IDR. 42,945,805.17/year, respectively. The average cattle farmer’s income from beef cattle farming in scales I, II, and III was IDR. 4,002,674.71/year; IDR. 9,482,032.71/year; and IDR. 19,716,588.39/year, respectively. The average contribution of beef cattle farming activity to the total income of farmers’ households in scales I, II, and III was 20.94%, 27.42%, and 47.00%, respectively. This study suggests that the farmers need to improve their economic management in order to survive or increase the income they derive from cattle farming. Farmers should also cooperate with Perhutani, a state forest company, as there are a number of ways in which the teak forest can support the sustainability of their cattle farming.